Abruptly Dogen - Smith, Kidder (punctum books, 2022)
"In the thirteenth century Dogen brought Zen to Japan. His tradition flourishes there still today and now has taken root across the world. Abruptly Dogen presents some of his pith writings-startling, shifting, funny, spilling out in every direction. They come from all seventy-five chapters of his masterwork, the Eye of Real Dharma (Shōbōgenzō 正法眼藏), and roam through mountains, magic, everyday life, meditation, the nature of mind, and how the Buddha is always speaking from inside our heads. An excerpt from chapter 1, "A Case of Here We Are": Human wisdom is like a moon roosting in water. No stain on the moon, nor does the water rip. However wide and grand the light, it still finds lodging in a puddle. The full moon, the spilling sky, all roosting in a single dewdrop on a single blade of grass. A man of wisdom is uncut, the way a moon doesn't pierce water. Wisdom in a man is unobstructed, the way the sky's full moon is unobstructed in a dewdrop. No doubt about it, the drop's as deep as the moon is high. How long does this go on? How deep is the water, how high the moon?"